Migrants’ Choice of Remittance Channel: Do General Payment Habits Play a Role? - Kosse, Anneke; Vermeulen, Robert (World Development, 2014)
Summary: This paper investigates the determinants in migrants’ choice of payment channel when transferring money to relatives abroad. We analyze survey results on 501 migrants in the Netherlands, identifying five remittance channels: bank, money transfer operator, in-cash transfers via informal intermediaries, ATM withdrawals abroad, and carrying cash abroad. The results show that education, costs, access, and financial development in the recipient country are important determinants, while general cash preferences and internet banking usage play a limited role. Based on our findings, financial education, cost reduction, and increasing financial inclusion may serve a valuable role to increase the use of formal channels.